A Jornada dos Vassalos, por D. Jerônimo de Ataíde em 1625 - Pablo Antonio Iglesias Magalhães (Navigator)
The present article identifies and analyzes a manuscript concerning the Day of the Vassals to restore the city of Salvador, invaded for the netherlanders in 1624. This study it discloses, still, the authorship of the text, until then anonymous, it inserts and it in the historiographic context of the netherlands wars in 1625.